Optimizing the Use of Ships in Time Charter to Increase the Efficiency of Coal Transportation at PT. Kartika Samudra Adijaya - Ramadhan, Wildan Fahri; Sudirman, Sudirman; Saputra, Toto Dwijaya (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
The Coal tugboat charter and private ownership have significant differences in various aspects, including control, cost, flexibility, and risks faced. In terms of control, when you choose to charter a ship, the charterer has control over the shipping route and schedule, but the technical and operational responsibilities remain with the shipowner. This means that although you can determine how and when the ship is used, you do not have full rights to manage the ship itself. On the other hand, by privately owning a vessel, the owner has full control over all operational aspects, including maintenance, operation and strategic decisions relating to the use of the vessel.